Constructing user participation for disabled people—the Norwegian context. Issue 9 (13th October 2022) - Guldvik, Ingrid; Askheim, Ole Petter
Abstract: The question raised in the article is how user participation and similar terms have been construed in policy for disabled people since the terms were introduced. The empirical base is Norwegian policy documents dealing specifically with policies relating to disabled people from the mid-1960s to the present. The study is based on a critical discourse analytical approach. The dominant discourses are characterised as 'varying discourses of democracy'. The discourses can be seen as illustrating mutual trust between citizens and the state in the Nordic welfare model. However, the harmony between citizens and the state is not necessarily sufficient to elicit great changes in political practices. The Nordic countries' reputation of 'being number one' in deinstitutionalisation and independent living might also conceal problems such as inflexible systems and the imbalance of power, whereby the control of services lies with the system and the professionals, not the users. Points of interest: The article analyses how user participation have been construed in policy documents for disabled people. Norwegian policy documents from the mid-1960s to present is the empirical base. The study is based on critical discourse analysis. The dominant discourses is characterised as varying discourses of democracy. The apparent harmony between the citizens and the state might conceal that the control lies with the system and the professionals, not the users.